Feasibility of the modified 30-second sit-to-stand test in an isolation ward of moderate COVID-19 (Medical Journal of Indonesia, 2021)
BACKGROUND The recovery after prolonged immobilization during hospitalization because of COVID-19 is the primary goal of moderate to severe COVID-19 rehabilitation. Lower extremity muscle function assessment after immobilization is needed before starting mobilization. Hence, this study aimed to evaluate the feasibility of the modified 30-second sit-to-stand test (m30STS) as one of the prospective tools of functional capacity assessment in moderate COVID-19. METHODS This cross-sectional study recruited the subjects consecutively. All eligible subjects with oxygen saturation (SaO2) ≥95% with or without oxygen supplementation performed the m30STS following the Bohannon’s guidelines. The score of m30STS was calculated based on the number of stands completed within 30 sec. A higher score of the m30STS indicated better lower extremity function. RESULTS Mean score of m30STS was 13.3. No subjects had oxygen desaturation or increased heart rate, and no fall incidents occurred. CONCLUSIONS The m30STS is feasible and safe to evaluate lower extremity for moderate COVID-19 patients with SaO2 >95%. The absence of oxygen desaturation and increase in heart rate showed no increased oxygen consumption during the test.